Biomedical colors images watermarking scheme based on LSB, Henon map and ECKBA - Noura Alexendre; Fotsing Kuetche; Welba Colince; Simo Thierry; Ntsama Eloundou Pascal (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
With rapid digitalization in healthcare, biomedical images like X-rays, CT, MRI, and ultrasound scans are routinely transmitted, stored, and shared across hospital networks and telemedicine platforms. Ensuring data security, authenticity, and patient privacy during this process is a major challenge. Unauthorized access, modification, or duplication of images can result in diagnostic errors, legal issues, and loss of patient trust. Researchers have developed algorithms for image watermarking (embedding copyright or authentication information) and image encryption (scrambling data to protect it) to address these concerns. In this article, we present an algorithm that combines watermarking with encryption to enhance security and ensure confidentiality for medical images. Our approach centers on a blind hybrid watermarking technique. 'Blind' means the original image is not needed to extract the watermark, and 'hybrid' refers to combining techniques. This method specifically uses LSB (Least Significant Bit) embedding with a text image as the watermark. For encryption, chaotic sequences generated by the Henon map (a mathematical system used to generate pseudo-random numbers) power selective encryption, while the Enhanced 1D Chaotic Key Based Algorithm (ECKBA) is used for image encryption. The main advantage is our method's ability to generate a large space of encryption keys, critical for resisting brute-force attacks. Experimental and planned results demonstrate the robustness of our algorithm against common attacks and its watermark's invisibility to the human eye